PIERRE BORDIEU’S HABITUS ANALYSIS OF THE “GOOD PRACTICE” LEARNING MODEL AT SD MUHAMMADIYAH SARILAMAK - Anggraini, Reski; Anugrah, Dendy Wahyu (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study analyzes the “good practice” learning model at SD Muhammadiyah Sarilamak through Pierre Bourdieu’s habitus theory to explain how Islamic educational practices cultivate students’ moral and behavioral dispositions. Employing a qualitative descriptive–analytical design, the research integrates observation, semi-structured interviews, and document analysis to explore how pedagogical programs such as the “One Thousand Daily Infaq,” “Friday Garbage Alms,” “Library Visit,” “Cheerful Friday,” and “Market Day” operationalize the interrelations among habitus, capital, and arena. The findings reveal that teachers act as agents who mobilize cultural, social, and symbolic capital to internalize Islamic virtues through repetitive, embodied practices that shape students’ enduring moral habitus. Theoretically, this study extends Bourdieu’s framework to Islamic education by demonstrating that moral development is a sociocultural process of embodied learning rather than a cognitive transfer of values. Practically, the “good practice” model provides a replicable paradigm for integrating character education into daily school culture, emphasizing community-based, value-oriented learning that supports ethical and social transformation. The study’s limitation lies in its single-site qualitative scope, indicating the need for comparative research across diverse educational settings to assess variations in habitus formation. Overall, this analysis confirms that SD Muhammadiyah Sarilamak’s learning model exemplifies how Islamic education can systematically construct moral subjectivity through the dialectical interaction of habitus, capital, and field, offering both theoretical enrichment and practical insights for moral pedagogy in the 21st century.